No differences in VO2max, O2-cost or performance between V1 and V2 skating techniques in moderate to steep inclinations - Losnegard, T.; Myklebust, H.; Hallén, J. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTtON: Traditionally, the primary ski skating technique in moderate uphill terrain has been the V2, whereas the V1 has been used in steeper inclines. However, in the recent years it is observable that some elite skiers have put more emphasis in use of the V2 technique even at steep uphill terrain. We therefore wanted to compare V1 against V2 concerning VO2max. O2-cost and performance at moderate to steep uphill terrain in elite cross country skiers.